Systematic review on self-care of individuals with type 1 Diabetes mellitus (Research, Society and Development, 2024)
According to the World Health Organization, type 1 diabetes is a chronic condition where the pancreas does not produce enough insulin. This investigation aims to carry out a systematic review on the importance of self-care for individuals with type 1 diabetes mellitus (DM1). This is a systematic review study, following the standards of the PRISMA declaration, to answer the guiding question mentioned in the introduction of the present study. Twelve investigations published in the last five years were included. The results of this study indicate that the importance of self-care for individuals with DM1 is based on preventing health problems, reducing health risks, reducing health service costs, improving patients' quality of life and minimizing health complications. Therefore, it is recommended that more studies be carried out on the subject in order to facilitate understanding of the topic and better disseminate knowledge about self-care in cases of DM1, its barriers and the ways in which self-care can be encouraged, improving also the approach of health professionals, the preparation of academics and the community's understanding of the subject.